Influence Of Age and Weight Of Gilt On Breeding Performance And Feed Intake During Gestation And Suckling Period - Kannan A (Department of Livestock Production Management, College of Veterinary and Animal Sciences, 1995)
An experiment was conducted to determine the influence of age and body weight of gilt on the breeding performance and feed intake during gestation and suckling period and to recommend an optimum age and body weight for breeding. Forty eight weaned female Piglings were randomly assigned into eight (A, B, C, D, E, F, G and H) groups each consisting of six. Pigs in group A, B, C and D were bred to designated boars on attaining seven, eight, nine and ten month of age. Similarly pigs in group E, F, G and H were bred to designated boars on attaining body weight of 70, 80, 90 and 100 kg respectively, irrespective their ages. Two pigs from each group were slaughtered within a week after mating and the genitalia were studied. The length, weight of uterus, ovarian weight and ovulation rate were increasing with increasing order of age and body weight of the animal. Remaining four pig in each of group were allowed to farrow and their litter performance was studied. The litter size, weight at birth and weaning were significantly (P < 0.01) different between the groups. The prepartum weight gain did not vary significantly in pigs of different age and weight. The weight at weaning significantly (P < 0.01) varied in pigs of different age and body weight at breeding. The food consumed during gestation period was not significantly different between groups while during suckling period it significantly (P < 0.01) varied with age and body weight at breeding. The onset of post weaning estrus did not vary significantly between groups. Overall results suggested that economic and optimum age and weight at breeding was nine months and 90 kg.